Dialect analysis of english - Evelyn Almeida; Anna Shkivera (Innova Research Journal)
The main purpose of this article is to understand better the phonology of a region/socioeconomic variety of English based on two recording from the International Dialects of English Archieve website (IDEA). As Hansen, Yapanel, Huang, & Ikeno (2004) state, â€œEvery individual develops a characteristic speaking style at an early age that depends heavily on his language environment (i.e., the native language), as well as the region where the language is spokenâ€ (p.1). In this study, we want to analyze how the speakerâ€™s pronunciation of English sounds is different from the English we know (American English) and how their intonation differs from the intonation patterns with which we are familiar. Finally, we want to analyze if the speakerâ€™s profile (age, education, gender, experience with English, and socioeconomic background) influence in their English pronunciation. For this study, we transcribed the recording in a written and a phonetic form using the International Phonetic Alphabet (IPA) and then we conducted a comparative analysis.